Budaya Agraris Dalam Konsep Idiom Bahasa Indonesia: Kajian Antropolinguistik - Syamsul Rijal (Universitas Mulawarman, 2018)
Language cannot be separated from culture. In fact, language is the cultural expression of a nation. An agrarian culture in Indonesian has undergone internalization, giving birth to new words and phrases. The results of this study show several words and phrases which are idioms in Indonesian with the process of internalization of agrarian culture. The words and phrases of the agrarian culture can be found in agricultural terms, for example lahan basah, membanting tulang, memeras keringat, panen, mencairkan, and others. These words and phrases have blended in people's minds and expressed everyday culture. Who knows who started and where it came from. However, the Indonesian language user community has accepted these terms as ancestral cultural heritage. Understanding idioms seems difficult if you only understand the meaning of conventions from Indonesian speakers. The semantic load contained in the concept of idioms is too long a derivative chain. Therefore, this paper bridges Indonesian language users to understand the concept of Indonesian idioms which is an internalization of the Indonesian agrarian culture itself.